Cruz Moqo dataset: Geometric and photogrammetric documentation of 138 stones from Cruzmoqo, Sacsayhuaman (Cusco, Peru) - Reyes Sevilla, Nancy (2025)
This dataset accompanies the article "Decoding Cruz Moqo: Geometric Analysis of Dispersed Stones from Early Inca (Killke) Construction at Sacsayhuaman" submitted to npj Heritage Science. It contains the complete geometric and photogrammetric documentation used for the manual and computational analyses of 138 dispersed stones from the Cruz Moqo sector, part of the Sacsayhuaman Archaeological Park in Cusco, Peru. The dataset includes: PDF: Inventory of stones with façade images, measurements, numbering, and basic metadata. DWG: Vector silhouettes of each stone façade. 3DM (Rhinoceros): Combined 3D model containing all vectorized façades. GH (Grasshopper): Algorithmic definition used to test stone arrangement through computational nesting. XLSX (Excel): Table listing each stone’s geometric descriptors (area, compactness, squareness, eccentricity). 3DM (Photogrammetric model): 3D model of the Cruz Moqo sector showing the spatial location and numbering of the documented stones. This dataset provides the minimal information required to reproduce and extend the geometric and computational analyses developed in the article.